SIBERNETIK DAN TEORI KONSTRUKTIVIS DALAM PENGAJARAN - Asnawi - (Mentari: Majalah Ilmiah Universitas Muhammadiyah Aceh, 2010)
A teacher should know a lot of theories that can be applied in teaching and learning process either English or other subjects. The current theories nowadays used by teachers are behaviorist theory, nativist approaches, computer-supported collaborative learning (CSCL) theories, cybernetics and constructivism theories. The focus of this article is to elaborate cybernetics and constructivism theories. The aim of this article is to briefly describe the cybernetics and constructivism theories in teaching and learning which covers the definition of cybernetics and constructivism, principles of constructivism learning, the characteristics of constructivism learning and teaching, the role of teachers and students, the challenging of teachers in constructivism classroom. Â Kew words: cybernetic, constructivism